Refleksi Pengalaman Perempuan dalam Memoar Berteman dengan Kematian karya Sinta Ridwan - Oktavira; Adek, Muhammad (Persona: Kajian Bahasa dan Sastra, 2024)
This research aims to reflect women's biological experience, women's language, women's psychology in the memoir Berteman dengan Kematian by Sinta Ridwan. This research uses the approach of Ginokritik Studies. The method used in this research is descriptive method with content analysis technique. The results of the data on the gynocritical analysis of the memoir Berteman dengan Kematian by Sinta Ridwan showed that there are three gynocritical models, namely: (1) women's biological experience, namely women's bodily experience, expressing all feelings, inner voices, women's desires, the appearance of the female body. (2) women's language expression, namely using their own style and language to model women's language, women's language can be seen from the aspects of conversation, intonation, and strategies in women's language (3) women's psychological experience, namely the experience and psychology of the author of all the emotions depicted in the work based on the author's psychological situation, female authors write stories with a background of suffering and madness as a form of expressing all the emotions that occur to women.